MODERNIMSE DAN KERUSAKAN LINGKUNGAN DALAM PERSPEKTIF ISLAM - afandi, arif fandi (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2020)
Environmental damage is a serious problem at this time. Environmental damage is caused by human activities themselves. We have felt the impact of environmental damage at this time. Weather anomalies, air, land and water pollution have become part of our daily lives. Environmental damage must be repaired immediately, because this concerns the sustainability of human life. Knowing the main causes of environmental damage is a must before repairing the damage. modernism turned out to be the main cause of environmental damage. Modernism is disastrous for human life because it separates between science and religion. In fact, religion, especially Islam, teaches people to always preserve the environment. Therefore, returning to the teachings of Islam is a solution to overcome environmental damage.